An analysis of demographic and pregnancy outcome data to explain non-attendance for postpartum glucose testing in women with gestational diabetes mellitus: Why are patients missing follow-up?. (June 2019) - Castling, Zora A; Farrell, Tom
Objectives: To identify significant differences in the demographic and pregnancy factors for women with gestational diabetes mellitus who attended or failed to attend for postpartum glucose testing. Study design: A database of 1052 patients with gestational diabetes mellitus was reviewed. The sample was divided into those who attended for postpartum glucose testing and those who did not. Demographic and obstetric outcomes for the two groups were compared. Results: Seventy-four per cent of patients who did not attend for postpartum glucose testing were in the two most deprived quintiles. Smokers, unemployed, younger women, those of higher parity and those who did not breast feed were less likely to attend. Conclusions: Failure to attend for postpartum glucose testing is associated with demographic factors reflective of deprivation. The opportunity to afford lifestyle changes and diabetes screening in these groups of women has been missed. Targeted patient education and accessible postpartum testing may improve compliance.